2012
DOI: 10.1179/1743133612y.0000000016
|View full text |Cite
|
Sign up to set email alerts
|

Grain refinement of as cast Mg–Mn alloy by simultaneous addition of trace Er and Al

Abstract: A novel method for the grain refinement of as cast Mg-1?8Mn alloy by simultaneous addition of trace Er and Al was developed. A series of Mg-Mn alloys with systematic additions of Er alone (Er) or simultaneously with Al (Er/Al) were designed in order to illustrate the effects of Er/Al on the microstructure of the Mg-Mn alloy. The results showed that significant grain refinement was obtained by simultaneous addition of Er/Al. The grain size decreased remarkably from over 800 mm in the unrefined alloy to 150 mm w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…Similar to other REEs, erbium (Er) has also been used in Mg alloys to enhance the corrosion resistance and mechanical properties. [138][139][140][141] According to the binary Mg-Er phase diagram, the equilibrium solid solubility of Er in the Mg matrix is 17.24 at % at the eutectic temperature. 113 Er can be dissolved in Mg during the solidication process, which reduces the axial ratio.…”
Section: Effects Of Rare Earth Elements (Rees) On the Corrosion Behav...mentioning
confidence: 99%
“…Similar to other REEs, erbium (Er) has also been used in Mg alloys to enhance the corrosion resistance and mechanical properties. [138][139][140][141] According to the binary Mg-Er phase diagram, the equilibrium solid solubility of Er in the Mg matrix is 17.24 at % at the eutectic temperature. 113 Er can be dissolved in Mg during the solidication process, which reduces the axial ratio.…”
Section: Effects Of Rare Earth Elements (Rees) On the Corrosion Behav...mentioning
confidence: 99%
“…EDS results also reveal that there is certain amount of Er dissolved in the α-Al matrix. Besides, it is found [12] that Al and Er have a stronger tendency than Mg-Er and Mn-Er to combine together, therefore there might be some Al3Er particles which can act as effective nuclei for the Er-containing alloy. 2) Er addition refines both the grain size and the Al6Fe phase.…”
Section: B Phase Constitutionmentioning
confidence: 99%
“…The addition of a small amount of rare Earth elements can significantly affect the microstructure and performances of Mg alloys. At present, rare Earth elements commonly added in biomedical Mg alloy include Nd ( Xie et al, 2021 ), Y ( Ren et al, 2017 ; Nie et al, 2021 ), Ce ( Amukarimi and Mozafari, 2021 ), La ( Ding et al, 2014 ), Er ( Zhang et al, 2010 ; Zhang et al, 2012a ), Gd ( Chen et al, 2019b ; Luo et al, 2020 ), etc. Nd can form new phases with Mg and other chemical elements in Mg alloys, thereby refining the microstructure and improving the mechanical performances of the alloys ( Xu et al, 2014 ).…”
Section: Modification Of Magnesium Alloys For Biomedical Applicationsmentioning
confidence: 99%
“…However, too much Y added to the alloy will lead to the formation of the MgY phase, forming many micro-batteries and accelerating the corrosion of the alloy. Although Ce, La, and Er have high cytotoxicity among rare Earth elements ( Feyerabend et al, 2010 ; Zhang et al, 2012a ), the addition of a small amount of above elements to Mg alloys will not damage human body, and can significantly improve mechanical performances and corrosion resistance ( Zhang et al, 2010 ). Chen et al (2019b) observed that when a low content of Gd (0%–1%) was added to the Mg-2Zn-0.5Zr alloy, the second phase was uniformly distributed, and the addition of Gd stabilized the degradation layer and reduced the degradation rate of the alloy.…”
Section: Modification Of Magnesium Alloys For Biomedical Applicationsmentioning
confidence: 99%